Industrial ecosystems: A systematic review, framework and research agenda - Burström, Thommie; Lahti, Tom; Parida, Vinit; Wincent, Joakim (Elsevier, 2024)
There is confusion surrounding the concept of industrial ecosystems (IEs). This research therefore presents a systematic literature review on the subject of industrial ecosystems and outlines several paths for future research. The paper defines the key characteristics of IEs, identifies three perplexity drivers that contribute to the conceptual ambiguity of IEs, proposes a four-tier integrative IE framework that outlines the core components of IE research, and presents a conceptual model that clarifies how synergetic effects emerge, leading to IE transformation. Articles are categorized into four categories (industrial symbiosis, metabolism, architecture, and orchestration) from which ten propositions are delineated. The study encourages researchers to tap into several areas from the view that this is a broad, but still rather unexplored area of research with high relevance for policy.
Keywords: Industrial ecosystem; Synergies; Policy; Review; Transformation; Sustainability; fi=Strateginen johtaminen|en=Strategic Management|